Avaliação clínica da eficiência e efeitos colaterais de duas técnicas de clareamento dental com peróxido de hidrogênio - Beloti, Maria Lucineia Fim (2015)
The aim of the present study was to assess clinically the effectiveness of at-home and in-office bleaching with hydrogen peroxide (HP) for color change (CC) and patient’s satisfaction (PS) with the outcome, and the side effects on dental sensitivity (DS) and alteration of enamel surface (AES). Thirty volunteers, age range from 18 to 25 years, participated in this research. The 7.5% and 35% HP gels (Total Blanc Home and Total Blanc Office, respectively) were used. Subjects were selected and randomly distributed into two groups: at-home bleaching group, with 2 applications for 20 min daily, for 4 weeks; in-office bleaching group, with 2 applications for 20 min/week, for 4 weeks. The color change measurements were performed at the upper right central incisor (tooth#11) through Vita Classical shade guide and Vita Easyshade spectrophotometer, in the following times: baseline (T0), immediately after dental bleaching (T1), and seven days after the dental bleaching (T2). The DS and PS with outcome were analyzed through illustrative scales, while the changes in the enamel surface were analyzed through portable surface roughness tester and scanning electron microscopy (SEM), using resin epoxy replicas of tooth#11, before and after bleaching. No statistically significant differences were found between both bleaching techniques for the CC through Vita Classical shade guide, PS with outcome (proportion test, p>.05) and DS (Mann-Whitney test, p>.05). For the CC through the spectrophotomer analysis, it was found higher percentage of B1 shade at the T1 and T2 after at-home bleaching, and higher percentage of A1 shade at T2 after in-office bleaching (proportion test, p.05). It was concluded that both bleaching techniques were effective in bleaching teeth, however the at-home bleaching provided whiter teeth when assessed through spectrophotometer. The DS found to be mild with both dental bleaching techniques, with no differences on PS with outcome of dental bleaching and on morphology and enamel surface roughness.